Computer support for team formation - Sierksma, G. (International Journal of Computer Science in Sport, 2002)
Team sports like football, ice hockey, basketball, baseball, and to a lesser extent also field hockey and volleyball, have become big business, and huge amounts of money are involved with the transfer of players. Beside that, everyone knows of a situation where, after being introduced with high expectations, a very expensive player turns out not to fit into the team and can be labeled as a "bad buy". Thus, it is no wonder that there is a growing interest in systems that support the decisions. The current computer systems are mostly used to generate statistics about the performance of teams and individual players. The systems, summarized under the name Computer Coach, go beyond this and are used for supporting coaches to determine the optimal line-up of teams and also support scouting crews for judging new players.